Student Media Usage Patterns and Non-Traditional Learning in Higher Education - Zawacki-Richter, Olaf; Müskens, Wolfgang; Krause, Ulrike; Alturki, Uthman; Aldraiweesh, Ahmed (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
A total of 2,338 students at German universities participated in a survey, which investigated media usage patterns of so-called traditional and non-traditional students (Schuetze & Wolter, 2003). The students provided information on the digital devices that they own or have access to, and on their usage of media and e-learning tools and services for their learning. A distinction was made between external, formal and internal, informal tools and services. Based on the students’ responses, a typology of media usage patterns was established by means of a latent class analysis (LCA). Four types or profiles of media usage patterns were identified. These types were labeled entertainment users, peripheral users, advanced users and instrumental users. Among non-traditional students, the proportion of instrumental users was rather high. Based on the usage patterns of traditional and non-traditional students, implications for media selection in the instructional design process are outlined in the paper.